The gender gap in executive promotions - Xu, Jing (Journal of Corporate Finance, 2024)
This paper examines whether there is a gender promotion gap among executives. Using a comprehensive dataset of executives, I find that women’s promotion probability is 16% lower than men’s after controlling for educational and employment background, age, function, rank, and firm characteristics. The gap occurs partially because women are clustered in positions that support the business rather than positions with profit-and-loss responsibilities. Additionally, my analysis shows that product market competition, public attention on gender diversity, a respectful corporate culture, and board gender diversity alleviate the gender promotion gap. These findings support the notion that demand-side factors continue to hinder women’s advancement to leadership positions.